Peculiarities of Application of Contact Methods for Measuring the Temperature of Technological Objects - Vasyl Fedynets; Ihor Vasylkivskyi (Energy Engineering and Control Systems, 2025)
Contact methods are usually used to measure the temperature of industrial technological objects. When using the contact method to create the necessary conditions for heat exchange, thermal transducer must be in direct contact with the object of study, the temperature of which must be measured. When measuring stationary temperatures, the readings must be taken after a certain time interval from the moment of contact of the thermal transducer with the object of study, when a state of thermal equilibrium is established between them. Measurement of non-stationary temperatures by contact methods is always associated with the occurrence of dynamic errors over time due to the thermal inertia of the thermal transducer. The complexity of the processes of interaction of thermal transducers with heat flows of different nature of the objects of study necessitates the construction of simplified models to obtain practical estimates of the measurement results. Therefore, the article proposes the principles of choosing a thermal transducer to reduce possible methodological errors and estimate the actual errors of measuring the temperature of the objects of study. The conditions that must be met when setting up and conducting experiments to obtain reliable temperature measurement results are given. The article contains reference and methodological materials on measuring the temperature of technological objects by contact methods.